Effects of stimulus emotional content on gaze pattern: An eye-tracking study - Andrés Castellanos-Chacón; Daniela Arias-Otero; Valeria Uribe-Jaramillo; Juan David Leongómez; Milena Vásquez-Amézquita (PLoS ONE, 2026)
The attentional system tends to prioritize negative stimuli in the early stages of processing, favoring threat detection. However, it is unclear whether this bias is maintained or reversed toward positive stimuli at later stages. In this study, we used a free-viewing paradigm with eye tracking to examine early and late attentional biases toward negative, positive, and neutral stimuli (humans in emotionally unloaded activities) versus control stimuli (inanimate objects) in 122 participants without affective disorders (64 men, 58 women). We fitted generalized linear mixed models with random intercepts for stimuli and random intercepts and slopes for participants, and used non-parametric bootstrap resampling to obtain robust estimates and confidence intervals. Additionally, the number of first fixations was analyzed with a COM-Poisson. Results showed that participants fixated faster ( χ 2 (3) = 97.55, p < .001) and for longer durations (χ 2 (3) = 337.45, p < .001) on negative stimuli compared to the other categories, confirming a negativity bias in early attention In late attention, we found longer total fixation durations ( χ 2 (3) = 200.24, p < .001) and a greater number of fixations ( χ 2 (3) = 207.02, p < .001) for negative stimuli, contradicting the hypothesis of a positivity shift during emotional regulation. This sustained negativity bias may reflect an adaptive regulatory process in which individuals allocate attentional resources to threat-related information to enhance learning and emotional preparedness. Future studies should examine these effects across diverse sociocultural settings and in clinical populations.